2007
DOI: 10.1002/art.22460
|View full text |Cite
|
Sign up to set email alerts
|

Arthritic pain is processed in brain areas concerned with emotions and fear

Abstract: Objective. Functional neuroimaging studies have shown that experimentally induced acute pain is processed within at least 2 parallel networks of brain structures collectively known as the pain matrix. The relevance of this finding to clinical pain is not known, because no direct comparisons of experimental and clinical pain have been performed in the same group of patients. The aim of this study was to compare directly the brain areas involved in processing arthritic pain and experimental pain in a group of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
148
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(161 citation statements)
references
References 44 publications
10
148
0
3
Order By: Relevance
“…Women had both lower sensation and pain thresholds than men after TKA [21]. Moreover, in a small study of only six men and six women with knee osteoarthritis, positron emission tomography imaging of the brain showed arthritic pain is processed in areas of the brain concerned with emotion and fear [15]. Certainly pain is complex and a detailed analysis of sex and gender differences in pain is beyond the scope of this article.…”
Section: Discussionmentioning
confidence: 91%
“…Women had both lower sensation and pain thresholds than men after TKA [21]. Moreover, in a small study of only six men and six women with knee osteoarthritis, positron emission tomography imaging of the brain showed arthritic pain is processed in areas of the brain concerned with emotion and fear [15]. Certainly pain is complex and a detailed analysis of sex and gender differences in pain is beyond the scope of this article.…”
Section: Discussionmentioning
confidence: 91%
“…The results showed that arthritic pain was associated with increased activity in the cingulate cortex, the thalamus, and the amygdale; areas involved with the processing of the emotional aspects of pain. Indeed, the authors suggested in this study that new treatments for pain in arthritis should target central structures (33).…”
Section: Discussionmentioning
confidence: 98%
“…The enhanced activity in the anterior cingulate is interesting in light of its proposed role in pain affect (Vogt, 2005;Kulkarni et al, 2007). The subcallosal portion is anatomically and functionally connected with the medial orbitofrontal and ventral posterior cingulate cortices (Vogt et al, 2006;Margulies et al, 2007), which in turn can be involved in self-monitoring and judgment about one's own and other individuals' emotional states (Ochsner et al, 2004;Vogt, 2005).…”
Section: Brain Regions Involved In the Observation Of Unpleasant Stimulimentioning
confidence: 99%